In memory of Prof. Dr. Karl Mais (1940-2012) - Kranjc, Andrej (Acta Carsologica, 2012)
Our friend, colleague, supervisor, chairman... our Charlie, who came back from the underground so many times, entered it the last time, without return. On January 25, 2012 the Earth opened for him, as would say the old Romans: “Mundus subterraneus patet”. Charlie will not come back, but for us, his colleagues and friends, he will stay among us for a long time. Wwhenever we will talk about past events, we shall say: “Charlie was with us ... Charlie organised ... it was Charlie’s idea ... Charlie took care for this ...” Archaeologist by education, caver, speleologist, karstologist, professor, “Hofrath”, head of the Speleological institute, co-worker of Vienna’s museum, chair of the International Speleological Union commission, organiser and Nestor of ALCADI ... for sure I cannot enumerate all. Probably I omitted more than I mentioned. For Acta carsologica it is more important to tell a little more about the contacts of Prof. Mais with Slovenia. He was a sort of a bridge between older generation of Austrian speleologists, just to mention G. Abel and H. Trimmel, who cultivated traditionally friendly contacts with Slovene cavers, where late F. Habe was the animator, and younger generation, where friendly contacts and reciprocal visits are no more the main topic, but are replaced by professional contacts and co-operation. Prof. Mais was very active at both sides. In Slovenia he attended professional meetings, congresses, and symposia, especially International Karstological School “Classical Karst”. In the 20 years of school existence he participated ten times, being one of the most frequent participants. I remember well his interesting, attractive and lively presented papers where he always told us something new and surprising related to history of karstology and speleology. He was always prepared to help. He took every question or demand for the advice very seriously, studied it and his answer brought much more than anybody expected; it did not matter whether the question was related to an important Austrian researcher from the 18th century or to a recently edited “karst” stamp. He liked to come to the Karst Institute at Postojna very much. Archives materials from Postojna were good supplement to his studies at Vienna’s archives. He had still many plans and wishes to realize regarding the history of karst research. We discussed open questions on Nagel, Hauer, Penck, Putick. Wwithout Karl’s help maybe we will never get the answers. Wwhen our journal Acta carsologica became oriented more towards international spheres, Prof. Mais co-operated as the author and as the reviewer. Between the years 1994-1999 he published four important papers on karst geomorphology and karst research history in Acta carsologica. At the University of Nova Gorica he was a supervisor of doctoral students, which was a very important help for this young university and even more for still younger programme of karstology. At the end I must mention that not only his professional knowledge but also his kind-heartedness, understanding, good wiliness, and optimism will be missed the most. Even in the most unpleasant situation, when the group of excursionists waited in front of the cave door and nobody had the key, or when he has to sleep in the car in front of the hotel where he booked the room and had to start to sort the slides at twilight because he was the first speaker at the symposium he remained in good mood. This is Charlie I will keep in my mind: smiling, gentle, and in good humour discussing and explaining complicated professional questions. Andrej Kranjc